Emergency Department Use by Women Experiencing Homelessness in Los Angeles, California, USA - Christine Samuel-Nakamura; Mary-Lynn Brecht; Rachel Arbing (Mary Ann Liebert, 2022)
Background: This article reports on the use of hospital Emergency Departments (EDs) in women experiencing homelessness in Los Angeles, California. Women 18 years of age or older were recruited from homeless day centers in Los Angeles to participate in this study. Materials and Methods: A self-report questionnaire on health status, demographics, and emergency service use was completed by study participants. Results: In this study of women experiencing homelessness, 64% utilized the ED within the past year. The mean number of ED use was 3.63 (range 0?20) visits in the past year. Higher frequency visits were significantly associated with several mental health conditions (p?=?0.016), physical disability (p?=?0.001), and traumatic brain injury (p?=?0.013). Conclusions: The physical and psychological impacts of the homelessness experience can be enormous, affecting the homeless individually and collectively. Study findings may help to understand how to improve services that support and meet the needs of women experiencing homelessness such as patient and family-centered care and trauma-informed care in the ED.